Characterization and optimization of bioactive compounds extracted from gum arabic via ultrasonic assisted technique - Mohammedelnour, Ahmed Adam Hassan (Kulliyyah of Engineering, International Islamic Universty Malaysia, 2020)
Gum Arabic is a natural antioxidant, which comes from Acacia complex group of gums (ACGG). It is rich in dietary fibres and polyphenolics compounds that can support healthy living due to its antioxidant activity (AA). Despite its rich AA and medical benefits, the research on the ACGG antioxidant extraction has not received the attention it deserves from researchers and governments. Therefore, the aim of this study is to create an optimized extraction conditions that will enhance antioxidant activity and effectiveness. To achieve this aim, the first experiment was conducted to extract the ACGG active compounds using methanolic crude extraction (MCE) method, and to determine the physiochemical properties of the extracts, e.g. flavonoids, phenolic compounds, moisture content, pH, metal profile and amino acid profile. Meanwhile, the second experiment was carried out to optimize the methods and extraction conditions to improve the AA using DOE and PCA. The third experiment was conducted to study the antioxidant materials regarding crude extract and its active sub-fractions using the optimized conditions, and the last experiment was carried out to investigate the anti-inflammatory of the ACGG methanolic crude extracts and active fractions (MF and AF) on Albino rats (in-vivo) and the antiproliferative activity against breast adenocarcinoma (MCF-7), colon adenocarcinoma (HCT-116), and prostate cancer (PC3) cell lines using in-vitro assay. Results from the extraction indicated a significant number of flavonoid compounds and phenolic compounds (amongst others) in both ACGG (6540±3.46µg/100g) and PBMT from (2560±3.49µg/100g) to (2710±4.04µg/100g), using HPLC analysis. The individual flavonoid detected was quercetin. For the phenolic acids, the active compound were identified in both the ACGG and the Prebio-T were caffeic acids and ρ-coumaric, p-hydroxybenzoic, and ferulic acid with caffeic acid being the most predominant phenolic compounds in the ACGG (lateritic soil sample: 401770±3.52µg/100g; clay soil samples: 77580±5.20 µg/100g). The optimization result showed that the maximum AA and yield of extract (predicted by Design Expert software 7.00) were 11.10% and 15.56% for Acacia seyal gum (ASG) and Prebio-T (PTC), respectively, using the ultrasonic extraction; and methanol at experimental temperature conditions of 43°C, power of 40 kHz, for 3 hrs. Furthermore, the GC-MS/MS results of the MCE, MF and AF of both ASG and PTC confirm the presence of a total of 57 bioactive compounds (BCs). Compared to the amounts of the same BCs were almost doubled in PTC methanol crude extract (MCE). The In-vivo results (i.e. acute inflammatory test) under control conditions in the laboratory at 300 mg/kg dosage of both MCE of ASG and PTC developed a mean and maximum percentage inhibition of 23.63% and 23.54% respectively, during the 24 hours observation using In-vitro methodology. The MCE of PTC resulted in strong cytotoxic activity (CA) against MCF7 cell lines with an IC50 value of 8.792 µg/ml. Compared to ASG, against MCF7, PC3, and HTC116 cell lines, showed IC50 values of 9.56, 11.53 and 13.36µg/ml, respectively. Furthermore, both MF and AF of PTC were found to possess the most efficient CA against PC3 cell lines that were stronger than the MF and AF of ASG with IC50 values of 9.56µg/mL and 9.63µg/mL, respectively. Finally, the antioxidant and antiproliferative properties of the bioactive compounds in GA have shown some evidence of effectiveness as traditional medicine as a preventive measure against the growth of cancer cell as well as acute inflammation.